Menilai Pemberian Opini Wajar Tanpa Pengecualian Atas Laporan Keuangan Pemerintah Daerah - Agustinus Salle; Hesty Theresia Salle; Klara Wonar (Universitas Cenderawasih, 2022)
This study seeks to investigate and exemplify the enhanced unqualified opinion of Indonesia's Regional Government Financial Reports. The increased number of unqualified opinions is distrustful due to widespread misusage of local government budgets. The research used the Semester Examination Results Overview (IHPS) published by the BPK as the data source. We assume that BPK's provide unqualified opinion according to the criteria: conformity of financial reports with Government Accounting Standards, the use of sound Internal Control Systems, the compliance to the laws and regulations, and the follow-up of the auditors' recommendations. The findings reveal that the unqualified opinions prove for some reasons, but some actualities do not support the opinions.